Haemostatic changes related to fibrin formation and fibrinolysis during the first trimester in normal pregnancy and in recurrent miscarriage - Marchi, Rita; Ramirez, Ysabel López; Nagaswami, Chandrasekaran; Masova, Leona; Pulido, Anibal; Mora, José López; Muller, Aixa; Arocha-Piñango, Carmen Luisa; Weisel, John W. (Thrombosis and Haemostasis, 2007)
We have studied some biophysical properties of the fibrin network during the normal state of pregnancy and in patients with recurrent miscarriage (RM), in the first trimester of pregnancy. The fibrin polymerization process, followed by turbidity, showed that the rate of fibrin monomer assembly and the final turbidity was increased in the pregnant group (normal and with history of RM) compared to non-pregnant women (normal and RM), which is consistent with the increased fibrinogen concentration during pregancy. No changes were observed in the Darcy constant (Ks) of RM clots, pregnant or not; however, in pregnant control subjects the Ks increased (p=0.03).The fibrin lysis rate was increased in pregnant women compared to non-pregnant, being faster in women with RM. The rheological properties of the fibrin network in the non-pregnant group (control and RM patients) were similar; in the pregnant state, the fibrin network of the control group was 1.3 times stiffer compared to the control non-pregnant women, and almost unchanged in RM patients. In this study we have found changes in the clot structure that seem to be related to normal pregnancy and an increased rate of the fibrin lysis process in the RM patients, which may have clinical relevance.
Keywords: Pregnancy; recurrent miscarriage; clot structure; internal fibrinlysis; rheological properties